2009
DOI: 10.1364/ol.34.002129
|View full text |Cite
|
Sign up to set email alerts
|

Spiraling zero-order Bessel beam

Abstract: The question that we are addressing concerns the possibility of creating a zeroth-order Bessel-like beam that spirals around the axis of propagation. The analytical features of the beam propagation are studied theoretically. Approximations to such a light field can be experimentally realized by using an axicon and a hologram. The beam potentially can attract interest in microfabrication applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 12 publications
0
33
0
1
Order By: Relevance
“…In contrast to these previous works, the optical twister has a single phase-dislocation along the optical axis with phase and amplitude profile spiraling as the beam propagates in free space. A spiraling zero-order Bessel beam has also been proposed using a spiral phase profile combined with an axicon [19]. Such beam, however, is not known to carry OAM and does not produce a continuous spiraling beam profile since the beam reverses in chirality after the focus.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to these previous works, the optical twister has a single phase-dislocation along the optical axis with phase and amplitude profile spiraling as the beam propagates in free space. A spiraling zero-order Bessel beam has also been proposed using a spiral phase profile combined with an axicon [19]. Such beam, however, is not known to carry OAM and does not produce a continuous spiraling beam profile since the beam reverses in chirality after the focus.…”
Section: Introductionmentioning
confidence: 99%
“…Although not strictly nondiffracting, such beams could be useful as hybrids between the two classes in applications such as microfabrication and optical tweezers. Interestingly, few recent works point toward this direction by proposing techniques to create Bessel-like beams with spiraling and snaking trajectories [10][11][12][13].…”
mentioning
confidence: 99%
“…Earlier works have showed that Bessel-like beam patterns can be delivered along sinusoidal [25] or spiraling trajectories [26]. An even earlier work suggested snaking beams made of the series cascade of the so-called sword beams [27].…”
Section: Introductionmentioning
confidence: 99%